2011
DOI: 10.1021/nn2015908
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Synthesis of a Core–Shell MWCNT/GONR Heterostructure for the Electrochemical Detection of Ascorbic Acid, Dopamine, and Uric Acid

Abstract: In this study, graphene oxide nanoribbons (GONRs) were synthesized from the facile unzipping of multiwalled carbon nanotubes (MWCNTs) with the help of microwave energy. A core-shell MWCNT/GONR-modified glassy carbon (MWCNT/GONR/GC) electrode was used to electrochemically detect ascorbic acid (AA), dopamine (DA), and uric acid (UA). In cyclic voltammograms, the MWCNT/GONR/GC electrode was found to outperform the MWCNT- and graphene-modified GC electrodes in terms of peak current. For the simultaneous sensing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
167
2
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(179 citation statements)
references
References 85 publications
2
167
2
4
Order By: Relevance
“…[1][2] Heterogeneous electron transfer (HET) at solid electrodes, including graphene, is the subject of many theoretical and methodological studies in electrochemistry. 3 Enhancement of the HET activity of graphene materials is key to realizing their potential applications in myriad important areas such as energy storage/conversion, [4][5][6] molecular sensing, [7][8] and electrocatalysis. [9][10][11] Moreover, there is growing interest in developing a deeper understanding of the fundamental electron transfer behavior of graphene materials, particularly the HET kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2] Heterogeneous electron transfer (HET) at solid electrodes, including graphene, is the subject of many theoretical and methodological studies in electrochemistry. 3 Enhancement of the HET activity of graphene materials is key to realizing their potential applications in myriad important areas such as energy storage/conversion, [4][5][6] molecular sensing, [7][8] and electrocatalysis. [9][10][11] Moreover, there is growing interest in developing a deeper understanding of the fundamental electron transfer behavior of graphene materials, particularly the HET kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…The synergistic effects of the MWCNT and the GONR result in an improved electrochemistry, as shown in the detection of ascorbic acid, uric acid and dopamine [22], p-dihydroxybenzene [23], polycyclic aromatic amines [24] or in biosensing [25].…”
Section: Introductionmentioning
confidence: 99%
“…[229] For electrocatalysis applications, the 32 doping of CNTs and graphene with heteroatoms to modulate their electronic structures and charge distributions 33 proved to be the key to improved catalytic activities. [132] For supercapacitor applications, band structure engineer-…”
mentioning
confidence: 99%
“…Sun et al [229] reported microwave-assisted synthesis of a core-shell MWCNT/graphene oxide 4 nanoribbon (GONRs) heterostructure (Figure 8a, 8c-8e). CV measurements (Figure 8b) show that GONR/GC 5 exhibits a much higher current density than does GC, MWCNT/GC, or graphene/GC.…”
mentioning
confidence: 99%
See 1 more Smart Citation